Developing e-learning for Kazakh National University - Kizi Imadildayeva, Aigul Zhaidarbek (2010)
Many universities in the world are implementing technology enhanced learning in order to improve education and help students to develop learning. Nowadays technology enhanced learning offers universities with all context of education and universities are trying to apply it. One such case is the Kazakh National University that is subject of this project. Kazakh National University as of the largest public university in Kazakhstan is meeting challenges to introduce technology enhanced learning. The university’s current system is not reliable; also it is outdated in terms of its structure; and need to be replaced with e-learning system. Octagonal theoretical model for e-learning has been used in order to lead this project. This model’s eight factors are grouped into three major domains: educational, technological and organizational. This model used as a guideline to observe the study by using a questionnaire and mail interviews as data collection techniques. This data collection was necessary as none of the interviewed individuals had experience with any e-learning systems. The analysis of the data shows positive attitude among the students and teachers for implementing an e-learning system. This proposed system is based on Moodle software and it is believed to be a full scale e-learning system that offers courses for students in Kazakh National University. Through user requirements, the project comes up with a reliable e-learning system that will help the KazNU’s administration manage courses and monitor students’ progress. Hence therefore the collaboration between students and staff would be improved with developed e-learning system.